Co-generation and the optimal steam/energy balance. - NOEL, E.L. Rene (1994)
Describes how Mauritius, a small island which is almost 100 percent dependent on imported fuels, has set about using bagasse for energy, how it intends optimising this use and what it hopes to achieve. Outlines technical parameters which are relevant in optimising plant configuration.